Probing dopant segregation in distinct cation sites at perovskite oxide polycrystal interfaces. Issue 1 (December 2017) - Yoon, Hye-In; Lee, Dong-Kyu; Bae, Hyung; Jo, Gi-Young; Chung, Hee-Suk; Kim, Jin-Gyu; Kang, Suk-Joong; Chung, Sung-Yoon
Abstract Although theoretical studies and experimental investigations have demonstrated the presence of space-charge-induced dopant segregation, most work has been confined largely to the crystal-free surface and some special grain boundaries, and to the best of our knowledge there has been no systematic comparison to understand how the segregation varies at different types of interfaces in polycrystals. Here, through atomic-column resolved scanning transmission electron microscopy in real polycrystalline samples, we directly elucidate the space-charge segregation features at five distinct types of interfaces in anAB O3 perovskite oxide doped withA - andB -site donors. A series of observations reveals that both the interfacial atomic structure and the subsequent segregation behaviour are invariant regardless of the interface type. The findings in this study thus suggest that the electrostatic potential variation by the interface excess charge and compensating space charge provides a crucial contribution to determining not only the distribution of dopants but also the interfacial structure in oxides. Space-charges in polycrystalline materials can drive segregation of dopants, however an in-depth understanding of this process is still missing. Here, the authors show that in polycrystalline perovskites the space-charge segregation and interfacial structure are nearly identical irrespective of the interface type.